TRADISI "BELE KAMPONG" MASYARAKAT KELURAHAN GADING SARI KECAMATAN KUNDUR KABUPATEN KARIMUN - Juliva Ningsih; Isjoni '; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRAK: Indonesia as an archipelago is a cluster of the longest and largest in the world which is always rich with cultural and pluralistic society comprising various tribes (ethnic), various religions and beliefs held by members of the public. Almost every tribe has its own language and traditions of different regions from each other. There is a tradition in the village of Kundur Gading Sari District of Karimun one of which is maintaining the tradition of the village in which the people Gading Sari as "bele kampong". In the implementation of the tradition itself there are symbols and terms of a bona fide religious significance for the people who carry out and believe in the purpose and function of the tradition. Bele kampong tradition is tradition in maintaining Gading Sari village or a ceremony mendo'a for the purpose of begging salvation or reject all the reinforcements that will befall the community with. Tradition "bele kampong" was conducted 1 (one) time in one year, exactly on December 3 and 6 Shaban. The exercise followed by Ivory Sari community both men, both old women to children. The purpose of this study was to determine the history of the tradition of "bele kampong" Gading Sari Village community Kundur District of Karimun, to investigate the implementation of a tradition "bele kampong" Gading Sari Village community Kundur District of Karimun, To know the meaning of the tradition of "bele kampong" Village community Gading Sari subdistrict Kundur Karimun, To find a community effort to preserve the tradition of "bele kampong" Gading Sari Village District of Kundur Karimun, to determine the public perception of the tradition "bele kampong" Gading Sari Village District of Kundur Karimun. Researchers used qualitative research methods for researchers looked at the social and cultural behavior in public life Gading Sari Village District of Karimun Regency Kundur of the process of tradition "bele kampong" held annually. Results from this research that in the current era development Gading Sari communities still carry that tradition a tradition rarely and even disappeared from public life. Gading Sari community have confidence that if it does not carry out the tradition of "bele village" will be a disaster, and in implementation have abstinence bans that must be endured by the people of Gading Sari.Keywords : Tradisi, Masyarakat, Bele Kampong